Structural Engineering Multiperiod Coating ZrN/MoN - Sobol, O. V.; Meylekhov, A. A.; Stolbovoy, V. A.; Postelnyk, A. A. (Sumy State University, 2016)
Using the method of structural engineering by changing the thickness of the layers in a multiperiod ZrN/MoN system investigated the effect of the phase-texture state of the crystallites and their size on the hardness of the vacuum-arc coating. Is revealed a determining influence on the formation of ZrN layers preferential orientation growth [100] axis with a small layer thickness 7-20 nm (the deposition of 3 to 10 seconds). At high layer thickness determines the texture [311] crystallites are - Mo2N phase formed in the Mo-N layers. Pulsed high-voltage stimulation without changing the type of structural states for different layer thicknesses, leads to partial disorientation texture in thick layers. Hardness of coating with thick (80 nm) layers is 35-37 GPa. In small thickness layers pulse stimulation of atoms motility causes the formation of a planar structure with an average crystallite size of 4-9 nm in the layers, which is accompanied by increased hardness of up to 44 GPa.

Використовуючи метод структурної інженерії шляхом зміни товщини шарів в багатоперіодній системі ZrN/MoN досліджено вплив фазово-текстурного стану кристалітів і їх розмір на твердість вакуумно-дугових покриттів. Виявлено визначальний вплив ZrN шарів на формування переважної орієнтації зросту з віссю [100] при малій товщині шарів 7-20 нм (час осадження 3 -10 сек). При великій товщині шарів визначальним текстуру [311] є кристаліти -Mo2N фази, що формується в Mo-N шарах. Імпульсна високовольтна стимуляція не змінюючи тип структурних станів для різних товщин шарів, призводить до часткової разорієнтації текстури при великій товщині шарів. Твердість покриттів з товстими (80 нм) шарами становить 35-37 ГПа. У шарах малої товщини імпульсна стимуляції рухливості атомів призводить до формування планарної структури з середнім розміром кристалітів в шарах 4-9 нм, що супроводжується підвищенням твердості до 44 ГПа.
Структурна інженерія багатоперіодних покриттів ZrN/MoN
Keywords: multilayer coating ZrN/MoN; the thickness of the layers; the bias potential; structure; crystallite nanosize; hardness; твердість; потенціал зсуву; нанорозмір кристалітів; товщина шарів; хімічні реакції